If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 3(x + 2) = 2 Reorder the terms: 2 + 3(2 + x) = 2 2 + (2 * 3 + x * 3) = 2 2 + (6 + 3x) = 2 Combine like terms: 2 + 6 = 8 8 + 3x = 2 Solving 8 + 3x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 3x = 2 + -8 Combine like terms: 8 + -8 = 0 0 + 3x = 2 + -8 3x = 2 + -8 Combine like terms: 2 + -8 = -6 3x = -6 Divide each side by '3'. x = -2 Simplifying x = -2
| 4(-2x+6)=72 | | 3(37)-x=74 | | 8x-141=19 | | 3(5x+8)=144 | | 9-16= | | 4(1x-8)=0 | | 5(4x+2)=-30 | | 2(6x-8)=68 | | 7(x+2)=5x+21 | | 5(6x+8)=-320 | | 8(x+2)-9= | | 3x+6=-82-5x | | -x+6=21-4x | | 8-x+5x-2-9x= | | 3x+4=-10+5x | | 3-7x=-5x-21 | | -2+5x+5x=68 | | 5x-3=5x+3 | | 4.3-1.4*(p+7)=-9.7 | | 7x-8+6x=-8 | | x+3+2x=39 | | 9+7x=58 | | 3*-1.33333333333+4/7= | | -1.33333333333+4/7= | | p(x)=x^2-256 | | -7[3+7(-4+7)]+15= | | 3r+4= | | 3r+4/7=1 | | -2+3x=10 | | 7x+1=-48 | | 5(-4)-(-17)= | | 3x-x=74 |